A “Fides Quaerens Intelectum: Perang Melawan Fundamentalisme Agama Perspektif Henri De Lubac” - Yohanes Alfrid Aliano; Urbanus Rohit (Jurnal Teologi dan Pelayanan Kerusso, 2023)
The focus of this study is to analyze and explore more deeply the Catholic faith in the fight against religious fundamentalism based on the thoughts of Henri De Lubac. There are several cases of deviation as a result of human misunderstanding in interpreting their religious teachings that parrot radicalism, apathy-worship of science and technology, moderate-conservative thinking and so on. Humans then believe blindly, meaning to interpret literally what is written in the faith rule without seeing, reflecting and reflecting more deeply on the intent and purpose of writing the fait rule. Then the faith that becomes blurred is often the background of violence, oppression, war and humiliation of human dignity. This paper aims to respond, reflect and understand more deeply the importance of having a critical awareness of reason and faith in combating faith radicalism. The author uses an interpretive descriptive method in the form of a literature review on the faith of Catholics based on Henri De Lubac's theological concepts in relation to Religious Fundamentalism by criticizing the faith that only blindly obeys and sticks to doctrine alone. The author finds that Religious Fundamentalism actually has a good purpose, but it is often misinterpreted, causing deviations. So, it is important to compare the elaboration of the basis of faith based on the locus teologicus of faith: the Bible, Tradition, Magisterium, and its contextualization. True Christian faith is an expression of complete surrender to God and being responsible for God's will in everyday life. Abstrak Indonesia Fokus studi ini menganalisis dan merefleksikan lebih dalam iman Katolik dalam memerangi fundamentalisme agama berdasarkan pemikiran Henri De Lubac. Ada berbagai kasus penyimpangan akibat dari kesalahpahaman manusia dalam mengartikan ajaran agamanya yang radikalisme, sikap apatis-pemujaan terhadap IPTEK, pemikiran konservatif-moderat dan semacamnya. Manusia lalu beriman secara buta, artinya menafsirkan secara harafiah apa yang tertulis di dalam regula imannya tanpa melihat, merefleksikan dan merenungkan lebih dalam maksud dan tujuan ditulisnya regula iman itu. Lantas iman yang menjadi kabur itu kerap kali melatarbelakangi terjadinya kekerasan, penindasan, perang dan perendahan martabat manusia. Tulisan ini bertujuan untuk menanggapi, merenungkan dan memahami lebih dalam akan pentingnya memiliki kesadaran kritis akal budi dan iman dalam memerangi radikalisme iman. Penulis menggunakan metode deskriptif-interpretatif berupa kajian pustaka tentang iman umat Katolik berdasarkan konsep teologi Henri De Lubac dalam kaitannya dengan Fundamentalisme Agama dengan mengkritisi iman yang hanya taat buta dan berpegang teguh pada doktrin semata. Penulis menemukan Fundamentalisme Agama sebenarnya memiliki tujuan yang baik, namun hal ini kerap kali disalahartikan sehingga menimbulkan penyimpangan berujung pada konflik. Maka, penting untuk mengkomparasi-elaborasikan dasar iman berdasarkan locus teologicus iman: Biblis, Tradisi, Magisterium, dan kontekstualisasinya. Iman Kristiani sejati itu merupakan ungkapan penyerahan diri kepada Allah secara utuh dan mau bertanggung jawab atas kehendak Allah dalam hidup setiap hari.